Source and genesis of Ca-Cl type brines in Qaidam Basin, Qinghai-Tibetan Plateau: evidence from hydrochemistry as well as B and Li isotopes - Li, Yongshou; Pan, Tong; Li, Hongpu; Cheng, Huaide; Zhang, Pengcheng; Han, Wenhua; Li, Binkai; Yuan, Qin; Ma, Xuehai; Ma, Haizhou (Frontiers in Environmental Science, 2024)
Ca-Cl brine is a highly mineralized special water body occurring in oceanic ridges or basins. The deep part of the western Qaidam Basin is rich in Ca-Cl brine, which is essential for the formation of (MgSO4-deficient) potash deposits. Previous studies on this type of brine in the Qaidam Basin focused on its source tracing, but different carriers led to different conclusions. Moreover, the genesis of Ca-Cl brines in inland basins still remains unclear. In essence, a solid understanding of the relatively abundant Ca sources for the formation of Ca-Cl brines in inland basins has not been reached. In addition, a metallogenic model for this type of brine has not yet been established. Through hydrochemical analysis as well as Band Li isotope tracing, this study clarified that the main elements (Na and Cl) in these Ca-Cl brines mainly originated from the dissolution of existing evaporites in the inner basin. Further, trace elements in Ca-Cl brines (such as Band Li) mainly originated from lixiviation; atmospheric rainfall infiltrated and interacted with ore-rich mother rocks along the basin-margin fracture system under suitable temperature-pressure conditions; alternatively, they may have originated from mixing with magmatic hydrothermal fluids. This study showed that Ca-Cl brines in the western part of the Qaidam Basin have a typical “binary structure” in terms of their sources. In addition, the sources of Ca in Ca-Cl brines were further discussed based on B and Li isotope data, thus exploring a new genesis of Ca-Cl brines in inland basins. Finally, by integrating the above findings, an ore-forming model of this type of water body in the western part of the Qaidam Basin is proposed. This study is valuable for understanding the genesis mechanism of Ca-Cl brines in inland basins, and also has practical significance for the prediction, exploration, and evaluation of this type of brine resource.